A Self‐Assembled Planar Chemical Garden in a 3D Solution. Issue 11 (19th March 2020) - Angelis, Georgios; Pampalakis, Georgios
Abstract: Addition of calcium chloride solution in sodium phosphate results in the formation of a closed chemobrionic bubble. Subsequent addition of sodium ethylenediaminetetraacetate results in the formation of radially growing fingers that finally yield new types of quasi‐2D chemical gardens that resemble waterlilies and trees. Abstract : Chemobrionics in 2D! A simple 3D CaCl2 /phosphate buffer system spontaneously self assembles into new 2D chemobrionics systems with structures that resemble waterlilies.